If it's not what You are looking for type in the equation solver your own equation and let us solve it.
Simplifying 2(y + 5) = y + 13 Reorder the terms: 2(5 + y) = y + 13 (5 * 2 + y * 2) = y + 13 (10 + 2y) = y + 13 Reorder the terms: 10 + 2y = 13 + y Solving 10 + 2y = 13 + y Solving for variable 'y'. Move all terms containing y to the left, all other terms to the right. Add '-1y' to each side of the equation. 10 + 2y + -1y = 13 + y + -1y Combine like terms: 2y + -1y = 1y 10 + 1y = 13 + y + -1y Combine like terms: y + -1y = 0 10 + 1y = 13 + 0 10 + 1y = 13 Add '-10' to each side of the equation. 10 + -10 + 1y = 13 + -10 Combine like terms: 10 + -10 = 0 0 + 1y = 13 + -10 1y = 13 + -10 Combine like terms: 13 + -10 = 3 1y = 3 Divide each side by '1'. y = 3 Simplifying y = 3
| 23=4x-x-10 | | (10x^2)+3=11x | | -3(n-6)=12(n-4)+7n | | 12y-15y=584 | | 8(t-4)+7t=5(3t+4)-8 | | -3x-3-x=21 | | 3x-3+4x+8=75 | | -3k-7=-22 | | -3(n-6)=12(n-4)+7 | | 10b+14-4b=-7-b | | -3(5t-2)+7t=5t-6 | | .5=1x-2(1.3x-4) | | 1.7-2.1a+4.5a=-6.7 | | 3x^2+32x+20=0 | | -3(n-6)=13(n-4)+7 | | 4(2x+3y)+2(4-x-3y)+2= | | 2x+7y=17.50 | | X+x-17=155 | | -3(2x-2)=-6x-6 | | 7x+2y=16.25 | | .20(y-9)+.14y=.12y-.7 | | 18r+-4r+9r+-5r=-18 | | (x-4)(7x+6)(x+7)(x-13)=0 | | 7-5x=14-6x | | X+y-4z=-1 | | -3(n-6)=(n-4)+7 | | 1+5x-2=19 | | 15x-15=15(x-3) | | 4k+24=6k-1 | | .25(10000)-0.02y=.08(y+10000) | | 6(2-x)(x+7)=0 | | 2x+9=x-8 |